2009
DOI: 10.1016/j.brainres.2009.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Polarized P-glycoprotein expression by the immortalised human brain endothelial cell line, hCMEC/D3, restricts apical-to-basolateral permeability to rhodamine 123

Abstract: Polarized P-glycoprotein expression by the immortalised human brain endothelial cell line, hCMEC/D3, restricts apical-to-basolateral permeability to rhodamine 123 Leon M. Tai This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 38 publications
4
52
0
Order By: Relevance
“…29,30 We established here, by quantitative confocal microscopy analysis of Podxl and P-gp expression in individual cells, that hCMEC/D3 cells are polarized on Transwell inserts (Figure 2), as previously reported by electron microscopy monitoring of P-gp expression. 23 We further demonstrated that siRNA-mediated PAR-3 knockdown largely prevented the apicobasal-polarized expression of these proteins. This result constitutes, to our knowledge, the first direct demonstration of the regulation by the Par/aPKC PCP complex of the apicobasal polarization of brain endothelial cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…29,30 We established here, by quantitative confocal microscopy analysis of Podxl and P-gp expression in individual cells, that hCMEC/D3 cells are polarized on Transwell inserts (Figure 2), as previously reported by electron microscopy monitoring of P-gp expression. 23 We further demonstrated that siRNA-mediated PAR-3 knockdown largely prevented the apicobasal-polarized expression of these proteins. This result constitutes, to our knowledge, the first direct demonstration of the regulation by the Par/aPKC PCP complex of the apicobasal polarization of brain endothelial cells.…”
Section: Discussionmentioning
confidence: 69%
“…Together with podocalyxin (Podxl), an apical marker of endothelial cells, the ABC-transporter P-gp, selectively expressed by brain endothelial cells, is highly enriched at their apical membrane; by contrast, the glucose transporter GLUT-1 is known to be expressed at apical and basal membranes of brain endothelial cells. 23 By confocal immunofluorescence analysis of these proteins, we then compared their apical versus basal expression in hCMEC/D3 cells after siRNA-mediated PAR-3 knockdown or after treatment with scrambled siRNA as control.…”
Section: Resultsmentioning
confidence: 99%
“…40 Moreover, these cells express chemokine receptors in response to inflammatory cytokines, a series of tight junction proteins 41 and multidrug resistant proteins, e.g., Pglycoprotein (P-gp). 42 Thus, hCMEC/D3 BBB models are an excellent candidate for blood-brain barrier function and transport studies. This human BBB model has been already widely utilized to test the delivery of neurotherapeutic molecules 43 and to study brain signalling mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…There are roughly 48 genes encoding the various human ABC transporters, each is organized into seven subfamilies designated ABCA to ABCG [103]. Over-expression of ABC transporters are major contributors to the development of multidrug resistance (MDR) in cancer cells.…”
Section: Atp-binding Cassette Transporters (Abc)mentioning
confidence: 99%
“…Under normal conditions, the presence of P-gp in the BBB limits a broad range of substances from penetrating the brain tissue. Some notable drug classes with reduced brain penetration due to P-gp efflux at the BBB include anti-epileptics, anti-cancer drugs, anti-histamines and HIV protease inhibitors [103]. Numerous studies using drugs such as cyclosporine, digoxin, domperidone, etoposide, loperamide, ondansetron, taxol and vinblastine have shown the important role of P-gp in the pharmacokinetics of P-gp substrates in multiple parts of the body.…”
Section: P-glycoprotein (P-gp)mentioning
confidence: 99%